On‐chip stimulated Brillouin Scattering for microwave signal processing and generation. Issue 5 (10th February 2014) - Pant, Ravi; Marpaung, David; Kabakova, Irina V.; Morrison, Blair; Poulton, Christopher G.; Eggleton, Benjamin J.
<x xml:space="preserve">Abstract</x> On‐chip realization of stimulated Brillouin scattering (SBS) enables photonic integration of microwave photonic signal processing and offers significantly enhanced performance and improved efficiency. On‐chip SBS is reviewed in the context of slow‐light based tunable delay, low‐noise narrow linewidth lasers and filtering for integrated microwave photonics. A discussion on key material and device properties, necessary to enable on‐chip Brillouin scattering using both the single‐pass and resonator geometry, is presented along with an outlook for photonic integration of microwave signal processing and generation in other platforms. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>